'Why Does This Make Me So Angry?': Using Self-Study to Uncover Hidden Epistemological Frames for Academic Identity Development. - Morettini, Brianne; Luet, Kathryn (Alternation, 2021)
This study explores how two female-presenting tenured faculty navigate the tensions of engaging in scholarship while also being tapped to fulfil intensive service obligations to their respective academic departments. In this way, we use our everyday lived experiences as associate professors to examine social cohesion and our own processes of becoming in our fluid academic identities. The purposes of this study are to use self-study to 1) explore the informal education of non-scripted work for tenured faculty; and 2) to uncover hidden epistemological frames for understanding our academic identity that are left otherwise subdued in the patriarchal contexts of higher education. Using sensemaking theory and post-structural feminism to theoretically frame our exploration, two critical friends engaged in a form of intimate scholarship to explore their post-tenure experiences of resisting patriarchal institutional norms that subjugate women to service roles. This study demonstrates an ontological commitment to methodological inventiveness that recognizes and validates the emotive aspects of experience and being. Key findings include the need for more widespread realizations of how emotionally engaged research is a fruitful way to explore social cohesion in the context of higher education in that it may uncover subjugated aspects of self in academic identity development.